An expanded MIL-53-type coordination polymer with a reactive pendant ligand. Issue 31 (18th July 2018) - Kunicki, Hannah; Chamberlain, Thomas W.; Clarkson, Guy J.; Kashtiban, Reza J.; Hooper, Joseph E.; Dawson, Daniel M.; Ashbrook, Sharon E.; Walton, Richard I.
Abstract : A bulky pendant pyridine- N -oxide ligand provides an expanded MIL-53 structure containing divalent framework cations with an extra-framework site for functionalisation. Abstract : A coordination polymer with a structure isoreticular to MIL-53, but containing a divalent metal cation (Co 2+ or Mg 2+ ) and a coordinating 4-styrylpyridine- N -oxide ligand, crystallises under solvothermal conditions; the pendant ligand can be brominated, with evidence from powder X-ray diffraction, element mapping and 81 Br solid-state NMR for this post-synthesis modification.